Geotermobarometria de Granulitos Associados à Supracrustais na Porção Norte do Complexo Guaxupé - Região de Arceburgo - Santa Cruz do Prata, MG - Nascimento, Magnólia Barbosa do [UNESP]; Oliveira, Marcos Aurélio Farias de [UNESP] (My University, 2012)
This paper is a contribution for the understanding of the geological evolution of Guaxupé Complex. New data on petrography and mineral chemistry as well as estimates of metamorphic (P-T) conditions in the region of Arceburgo - Santa Cruz do Prata (MG) Brazil, at the southern portion of the Brasília Belt, more specifically at the Guaxupé Complex (Domain) are now presented. The lithotypes are high-grade metamorphic rocks subdivided into two groups: metasediments and granulites (orthoderivates). Chemical analysis of minerals was performed in three steps including core and rim of amphibole, pyroxene, feldspar, biotite, and garnet from samples of the following rock types: enderbites, mafic granulites, charnockites, and alkali feldspar charnockites. Results obtained with geothermobarometric calculations show metamorphic peak around 900°C of T and 10 kbar of P. Enderbites and tonalite granulites (mafic) show the highest values of temperature and pressure, while alkali feldspar charnockites show the lowest probably due to their late generation in relation to mafic rock types (enderbites and mafic tonalite granulite). Chemical mineral analysis in metamorphic parageneses and geothermobarometric calculations indicate that the possible metamorphic peak may be higher than 900°C of temperature and around 10 kbar of pressure, within a isothermal decompression (ITD) regime.

O trabalho proposto visa contribuir para o entendimento da evolução geológica do Complexo Guaxupé com novos dados a cerca da petrografia e da química mineral, além de proceder às estimativas das condições metamórficas de litotipos na região de Arceburgo – Santa Cruz do Prata (MG), dentro da porção sul da Faixa Brasília e, mais especificamente, do Complexo (Domínio) Guaxupé. Os litotipos encontrados são rochas metamórficas de alto grau subdivididas em dois grupos: rochas metassedimentares e granulitos (ortoderivadas). As análises químicas dos minerais foram executadas em três etapas incluindo centro e borda de anfibólios, piroxênios, feldspatos, biotita e granada das amostras dos seguintes litotipos: enderbitos, granulitos máficos, charnockitos e álcali feldspato charnockitos. Resultados obtidos nos cálculos geotermobarométricos indicam pico metamórfico em torno de 900°C para T e 10 kbar para P. Enderbitos e granulitos tonalitos (máficos) apresentam os maiores valores de temperatura e pressão, enquanto que charnockitos e álcali feldspato charnockitos apresentam temperaturas e pressões mais baixas, provavelmente em função de sua geração tardia em relação aos litotipos máficos (enderbitos e granulitos tonalitos-máficos). A análise do metamorfismo nas paragêneses minerais exibidas pelas rochas e, os cálculos geotermobarométricos indicam que é possível o pico metamórfico dessas rochas ter ocorrido a mais de 900°C de temperatura e em torno de 10 kbar de pressão, dentro de um regime de descompressão isotérmica (ITD).
Geothermobarometry of granulites associated with supracrustal in the northern portion of the Guaxupé Complex - Arceburgo - Santa Cruz do Prata, MG
Keywords: Granulites; Guaxupé Complex (Domain); High grade metamorphism; Thermobarometry; geobarometry; granulite; high pressure; high temperature; metamorphic rock; metamorphism; paragenesis; petrography; Arceburgo; Brazil; Minas Gerais; Santa Cruz do Prata